Acoustic Analysis of the Effects of Vapor-Liquid Interfacial Morphology on Pool-Boiling Heat Transfer. (3rd August 2022) - Almadih, Mustafa H.; Almudhhi, T.; Ebrahim, S.; Howell, A.; Garrett, G. R.; Bajorek, S. M.; Cheung, F. B.
Abstract: In this study, boiling regimes have been identified and analyzed along with the corresponding vapor-liquid interfacial morphologies and heat transfer behaviors during quenching of a heated rod using an acoustic measurement technique. The quenching experiments are performed by using cylindrical test samples that are embedded with thermocouples. The experimental work includes investigating the whole range of pool boiling regimes from film boiling through transition boiling to nucleate boiling using Python's tools of signal processing. The boiling signals are recorded by a special hydrophone (i.e., the HTI-96-Min Exportable, High Tech, Inc.) to register the different sound waves generated by boiling under the water. This special hydrophone is capable of working in boiling water to record high- and low-frequency signals in subcooled pool boiling. The latter has many applications, such as the operations of advanced nuclear reactors, chemical processing, power generation, etc. In this work, the technique of signal processing is employed to identify the boiling regimes and to seek a new understanding of the boiling dynamics, particularly vapor-liquid interfacial morphologies, by applying a new tool for signal processing. Physically, each boiling regime should have a characteristic dominant acoustic signal that can be identified. By correlating the acoustic signatures with the boiling heat fluxes in various regimes, the minimum and maximum heat fluxes measured during the quenching of the cylindrical samples can be identified from the recorded acoustic signals during subcooled pool boiling.